GABAergic Control of the HPA axis as a Treatment Target for Epilepsy. - Wakefield, Seth. (2017)
Abstract: In response to stress, the hypothalamic pituitary adrenal (HPA) axis is activated and the stress hormone corticosterone is released from the adrenal gland in mice. Stress is a common trigger for seizures, and epileptic patients have increased levels of stress hormones. We hypothesize that HPA activation following a single seizure episode may result in future seizure susceptibility due to the pro-convulsant effects of corticosterone. Our data demonstrate that a single seizure episode is sufficient to activate the HPA axis and increase circulating levels of corticosterone. Consistent with the pro-convulsant effects of corticosterone, attenuating the output of the HPA axis reduced seizure susceptibility. Our data suggest that increased levels of corticosterone during and following seizures could be mediating the creation of a pro-epileptic environment. Thus, insight into the regulation of the HPA axis associated with seizure activity might have significant implications for seizure control. Neurons controlling the HPA axis are largely regulated by GABAergic inhibition. The chloride co-transporters KCC2 and NKCC1 maintain the chloride gradient which is essential for GABAA mediated hyperpolarization. Here we demonstrate that KCC2 is down-regulated and functionally impaired, and NKCC1 up-regulated, in the paraventricular nucleus (PVN) of the hypothalamus, compromising GABAergic inhibition and contributing to HPA hyperexcitability following seizures. Further our data suggest that treatment with the NKCC1 inhibitor bumetanide decreases seizure susceptibility in adult animals. These data suggest that impaired GABAergic inhibition in neurons controlling the HPA axis create a pro-epileptic environment and bumetanide may be a novel target for seizure control.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the Dept. of Neuroscience.; Advisor: Kathleen Dunlap.; Committee: Chris Dulla, Stephen Moss, and Jamie Maguire.; Keyword: Neurosciences.